A generalized Lyapunov's inequality for a fractional boundary value problem - Chidouh, Amar
We prove existence of positive solutions to a nonlinear fractional boundary value problem. Then, under some mild assumptions on the nonlinear term, we obtain a smart generalization of Lyapunov's inequality. The new results are illustrated through examples. © 2016 Elsevier B.V.